Mitochondrial dysfunction and mitophagy defect triggered by heterozygous GBA mutations. Issue 1 (2nd January 2019) - Li, Hongyu; Ham, Ahrom; Ma, Thong Chi; Kuo, Sheng-Han; Kanter, Ellen; Kim, Donghoon; Ko, Han Seok; Quan, Yi; Sardi, Sergio Pablo; Li, Aiqun; Arancio, Ottavio; Kang, Un Jung; et al.
ABSTRACT: Heterozygous mutations in GBA, the gene encoding the lysosomal enzyme glucosylceramidase beta/β-glucocerebrosidase, comprise the most common genetic risk factor for Parkinson disease (PD), but the mechanisms underlying this association remain unclear. Here, we show that in Gba L444P/WT knockin mice, the L444P heterozygous Gba mutation triggers mitochondrial dysfunction by inhibiting autophagy and mitochondrial priming, two steps critical for the selective removal of dysfunctional mitochondria by autophagy, a process known as mitophagy. In SHSY-5Y neuroblastoma cells, the overexpression of L444P GBA impeded mitochondrial priming and autophagy induction when endogenous lysosomal GBA activity remained intact. By contrast, genetic depletion of GBA inhibited lysosomal clearance of autophagic cargo. The link between heterozygous GBA mutations and impaired mitophagy was corroborated in postmortem brain tissue from PD patients carrying heterozygous GBA mutations, where we found increased mitochondrial content, mitochondria oxidative stress and impaired autophagy. Our findings thus suggest a mechanistic basis for mitochondrial dysfunction associated with GBA heterozygous mutations. Abbreviations: AMBRA1: autophagy/beclin 1 regulator 1; BECN1: beclin 1, autophagy related; BNIP3L/Nix: BCL2/adenovirus E1B interacting protein 3-like; CCCP: carbonyl cyanide 3 -chloroyphenylhydrazone; CYCS: cytochrome c, somatic; DNM1L/DRP1: dynamin 1-like; ER: endoplasmic reticulum; GBA: glucosylceramidase beta; GBA-PD: Parkinson disease with heterozygous GBA mutations; GD: Gaucher disease; GFP: green fluorescent protein; LC3B: microtubule-associated protein 1 light chain 3 beta; LC3B-II: lipidated form of microtubule-associated protein 1 light chain 3 beta; MitoGreen: MitoTracker Green; MitoRed: MitoTracker Red; MMP: mitochondrial membrane potential; MTOR: mechanistic target of rapamycin kinase; MYC: MYC proto-oncogene, bHLH transcription factor; NBR1: NBR1, autophagy cargo receptor; Non-GBA-PD: Parkinson disease without GBA mutations; PD: Parkinson disease; PINK1: PTEN induced putative kinase 1; PRKN/PARK2: parkin RBR E3 ubiquitin protein ligase; RFP: red fluorescent protein; ROS: reactive oxygen species; SNCA: synuclein alpha; SQSTM1/p62: sequestosome 1; TIMM23: translocase of inner mitochondrial membrane 23; TOMM20: translocase of outer mitochondrial membrane 20; VDAC1/Porin: voltage dependent anion channel 1; WT: wild type